Fibrinogen-clotting enzyme, pictobin, from Bothrops pictus snake venom. Structural and functional characterization - Vivas-Ruiz, Dan E. (2020)
A thrombin-like enzyme, pictobin, was purified from Bothrops pictus snake venom. It is a 41-kDa monomeric glycoprotein as showed by mass spectrometry and contains approx. 45% carbohydrate by mass which could be removed with N-glycosidase. Pictobin coagulates plasma and fibrinogen, releasing fibrinopeptide A and induces the formation of a friableiporous fibrin network as visualized by SEM. The enzyme promoted platelet aggregation in human PRP and defibrination in mouse model and showed catalytic activity on chromogenic substrates S-2266, S-2366, S-2160 and S-2238. Pictobin interacts with the plasma inhibitor alpha 2-macroglobulin, which blocks its interaction with fibrinogen but not with the small substrate BApNA. Heparin does not affect its enzymatic activity. Pictobin cross reacted with polyvalent bothropic antivenom, and its deglycosylated form reduced its catalytic action and antivenom reaction. In breast and lung cancer cells, pictobin inhibits the fibronectin-stimulated migration. Moreover, it produces strong NADH oxidation, mitochondrial depolarization, ATP decrease and fragmentation of mitochondria! network. These results suggest by first time that a snake venom serinprotease produces mitochondrial dysfunction by affecting mitochondrial dynamics and bioenergetics. Structural model of pictobin reveals a conserved chymotrypsin fold beta/beta hydrolase. These data indicate that pictobin has therapeutic potential in the treatment of cardiovascular disorders and metastatic disease.